Determination of random pore model parameters for underground coal gasification simulation. (1st January 2019) - Iwaszenko, Sebastian; Howaniec, Natalia; Smoliński, Adam
Abstract: Gasification technologies represent the most viable options of thermochemical processing of solid fuels. They are also characterized by lower emissions and higher efficiency when compared to conventional combustion systems. Particular attention has been paid to underground coal gasification offering the possibility of utilization for energy purposes coal resources otherwise inaccessible for economic or safety reasons. The disadvantage of this process is, however, the difficult control both in terms of technological and environmental aspects. The underground coal gasification process requires investigation of numerous heterogeneous reactions and transport processes, influenced by various process parameters, such as the temperature, type and flow rate of a gasification agent and geological conditions of the georeactor. In the paper a new, alternative way of the determination of kinetics of coal gasification by the Random Pore Model application is proposed. The procedure for determination of model parameters is presented. The structural parameter was estimated on the basis of measurements of char porous structure parameters. The reactivity measurements made for selected Polish coals were applied in determination of kinetic constants. The results of gasification process simulations for determined parameters and Random Pore Model are also given. Highlights: Random Pore Model (RPM) application in modeling of underground coal gasification. Determination of RPM structural parameter ψ based on coal char porosity measurements. Determination of RPM kinetic constant for selected Polish coals based on reactivity measurements. RPM simulation of coal gasification process within the selected range of variables. Sensitivity analysis for reaction rate changes vs structural parameter ψ variations.